EXPLANATIONS OF SOME LEXEMS AND WORDS SPECIFIC TO THE CURRENT UZBEKISTAN PHRASEOLOGISMS - Abduvaliyeva Madina,Kazokova Sayyora (International Journal of Literature and Language Studies, 2026)
This article analyzes certain lexemes and dialectal words found in the phraseological units of the modern Uzbek language. The study examines the role of phraseological units in the language system, their semantic characteristics, and the use of dialectal and historical lexemes within stable expressions. Through illustrative examples, the meanings of dialectal components and their significance in contemporary speech are revealed.